Ecological and public health dimensions of ESBL-producing Escherichia coli in bats: A One Health perspective - Alfiana Laili Dwi Agustin; Aswin Rafif Khairullah; Mustofa Helmi Effendi; Wiwiek Tyasningsih; Ikechukwu Benjamin Moses; Budiastuti Budiastuti; Hani Plumeriastuti; Sheila Marty Yanestria; Katty Hendriana Priscilia Riwu; Fidi Nur Aini Eka Puji Dameanti; Wasito Wasito; Riza Zainuddin Ahmad; et al. (Veterinary World)
Background and Aim: The emergence and global dissemination of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli represent a major public health concern. While antibiotic resistance in clinical and agricultural settings is well documented, the contribution of wildlife, particularly bats, to the spread of antimicrobial resistance (AMR) remains underexplored. Bats possess unique ecological traits – such as long-distance flight, longevity, and adaptability – that facilitate their role as potential reservoirs and vectors of antibiotic-resistant bacteria. This review synthesizes global findings on the occurrence, genetic characteristics, and transmission dynamics of ESBL-producing E. coli isolated from bats. Through a comprehensive literature review of studies conducted across five continents, we highlight the prevalence of multidrug-resistant E. coli in bat populations, with resistance profiles frequently including β-lactams (bla), aminoglycosides, tetracyclines, and fluoroquinolones. Notably, key ESBL genes such as blaCTX-M, blaTEM, blaSHV, and blaOXA have been identified in isolates from bat feces (guano), raising significant concern due to potential environmental contamination and zoonotic spillover. Risk factors such as habitat encroachment, anthropogenic waste exposure, and the agricultural use of bat guano further exacerbate the risk of ESBL transmission. Moreover, genomic comparisons suggest phylogenetic overlap between ESBL-producing E. coli from bats and those found in humans and livestock. Given these findings, bats warrant greater inclusion in One Health surveillance frameworks to trace AMR gene flow and develop targeted interventions. This review underscores the need for integrated AMR monitoring in wildlife, enhanced waste management policies, and stricter biosecurity to mitigate the public health risks associated with wildlife-origin ESBL dissemination.